Antibacterial, antifungal and anti-inflammatory activities of Melia azedarach ethanolic leaf extract (Bangladesh Journal of Pharmacology, 2016)
The aim of the present study is to examine the antibacterial, antifungal and anti-inflammatory activities of the ethanolic leaf extract of Melia azedarach. It was tested in vitro for its antibacterial and antifungal activities against E. coli (ATCC 8739), Enterococcus faecalis (Ec P07) and Bacillus subtilis (Bs) bacteria as well as against pathogenic fungi (Alternaria alternate, Fusarium solani, Fusarium oxysporum sp. melonis, F. oxysporum f. sp. lycopersici, F. sambucinum and Botrytis cinerea) with different techniques similtaneously with anti-inflammatory activity with carageaneen method. All tested concentrations of M. azedarach extract showed significant antibacterial and antifungal activities with low IC50 compared to ethanol 95% and a high anti-inflammatory activity compared with indomethacin as drug. Our investigation pointed that M. azedarach could be considered as a good medicinal agent.Video Clip of Methodology:Anti-inflammatory effect: 3 min 03 sec   Click to watch